The tender reader, or, trivializing Flannery O’Connor - Williamson, Beata (Litteraria Copernicana, 2025)
In this study, I interpret five short stories from Flannery O’Connor’s first published collection, A Good Man Is Hard to Find (1955): “The Life You Save May Be Your Own,” “A Stroke of Good Fortune,” “A Temple of the Holy Ghost,” “A Late Encounter with the Enemy,” and “Good Country People.” Each of the stories contains elements of the macabre, biting humor, or physical and psychological violence, so characteristic for the writer. Yet, less characteristically, each of them ends somewhat positively, sparing the reader the feeling of discomfort, which O’Connor usually serves. Thus encouraged, in search of apparently insignificant readerly comforts, I analyze the stories through the perspective of emotions, arguing that her repulsive, grotesque characters take on human qualities when viewed with compassion. O’Connor’s texts contain considerable evidence that allows for the above reading. In this interpretation, the horror and disgust traditionally associated with the author’s characters are replaced by tenderness, and the audience feels joy in discovering that the characters manage to defend themselves from dehumanization.